Guided Inquiry and Consensus-Building Used to Construct Cellular Models - Joel I. Cohen (American Society for Microbiology, 2015)
Using models helps students learn from a “whole systems” perspective when studying the cell. This paper describes a model that employs guided inquiry and requires consensus building among students for its completion. The model is interactive, meaning that it expands upon a static model which, once completed, cannot be altered and additionally relates various levels of biological organization (molecular, organelle, and cellular) to define cell and organelle function and interaction. Learning goals are assessed using data summed from final grades and from images of the student’s final cell model (plant, bacteria, and yeast) taken from diverse seventh grade classes. Instructional figures showing consensus-building pathways and seating arrangements are discussed. Results suggest that the model leads to a high rate of participation, facilitates guided inquiry, and fosters group and individual exploration by challenging student understanding of the living cell.